Pengenalan Konsep Peramalan Permintaan Pada Pelaku UMKM Kecamatan Sidayu Kabupaten Gresik - Dzakiyah Widyaningrum; Elly Ismiyah; Moh. Nuruddin (Universitas Katolik Widya Karya Malang, 2023)
The SMEs sector has an important role in supporting economic development in Indonesia. One of the sub-districts in Gresik, namely Sidayu, has many SMEs that are members of an association called ASUMSI. Almost all SMEs in these locations have not carried out a structured production planning. Production planning plays a vital role in a product-producing industry, including SMEs. Production planning can be started by forecasting demand. The results of this demand forecasting become the basis for production planning. This community service takes the theme of introducing the concept of demand forecasting which is expected to improve the production planning process for SMEs. This community service is carried out through counseling regarding the basic concept of demand forecasting for SMEs actors who are incorporated in ASUMSI. This community service is a form of academic participation in increasing the capacity of local resources, namely SMEs